Ultrasound Evaluation of Chronic Venous Insufficiency - Vallejos-Vidal, E (LIPPINCOTT WILLIAMS & WILKINS, 2023)
Chronic venous insufficiency is a common condition caused by valvular incompetence and/or obstruction of the lower extremity venous system. Chronic venous insufficiency presents in a wide range of clinical presentations, ranging from mild pain or edema to the development of varicose veins and nonhealing venous ulcers. Doppler ultrasound is the preferred imaging modality in the assessment of this condition and provides both anatomical and functional information in a noninvasive, cost-effective, and radiation-free manner. Knowledge of the anatomy and nomenclature, pathophysiology, equipment requisites, scanning protocols, relevant findings, and reporting nuances is essential to the creation of an accurate and clinically actionable report. Evaluation of the superficial and deep venous system for degree and extent of reflux is necessary to establish the diagnosis and to institute appropriate treatment.